PENGELOLAAN SAMPAH SAYURAN MENJADI PUPUK KOMPOS DI SMA MUHAMMADIYAH KOTA JAYAPURA - Midah Nurhidayah; Ardian Hangga Kelana; Sittin Masawoy; Febri Listianingrum (Bajang Institute, 2024)
Community Service Activities (PKM) aim to empower students in managing vegetable waste into compost at SMA Muhammadiyah Kota Jayapura. The results of community service activities (PKM) include: (1) students know the benefits of utilizing compost from vegetable waste that can help the economy and overcome environmental pollution. (2) through socialization and training, students can process vegetable waste into compost independently. The tools used in making compost include plastic buckets and lids, cloth, gloves, shovels, brooms, and rakes. The materials needed to make compost are organic waste (vegetables and fruit peels that have been chopped), sawdust, brown sugar solution, water, a solution containing microbes (EM-4), and mature compost. This composting process takes 2 weeks and after that the compost is ready to use. The management of vegetable waste into compost has been proven to be able to increase the use of waste in everyday life and is one of the solutions to environmental problems